2023
DOI: 10.1186/s12913-023-09955-x
|View full text |Cite
|
Sign up to set email alerts
|

Transformation to a patient-centred medical home led and delivered by an urban Aboriginal and Torres Strait Islander community, and association with engagement and quality-of-care: quantitative findings from a pilot study

Saira Mathew,
Federica Barzi,
Anton Clifford-Motopi
et al.

Abstract: Background The patient-centred medical home (PCMH) is a model of team-based primary care that is patient-centred, coordinated, accessible, and focused on quality and safety. In response to substantial population growth and increasing demand on existing primary care services, the Institute for Urban Indigenous Health (IUIH) developed the IUIH System of Care-2 (ISoC2), based on an international Indigenous-led PCMH. ISoC2 was piloted at an urban Aboriginal and Torres Strait Islander Community-Cont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Community members' experiences of more contact with health staff was supported by the quantitative evaluation of the pod model, which found that patients assigned to a care team were more likely to have continuity-of-care and increased contact with an AHW (Mathew et al 2023). The increased contact with an AHW is particularly encouraging, given the lived and embodied Indigenous knowledges they bring to their health care role (Stajic 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Community members' experiences of more contact with health staff was supported by the quantitative evaluation of the pod model, which found that patients assigned to a care team were more likely to have continuity-of-care and increased contact with an AHW (Mathew et al 2023). The increased contact with an AHW is particularly encouraging, given the lived and embodied Indigenous knowledges they bring to their health care role (Stajic 2020).…”
Section: Discussionmentioning
confidence: 98%